Women's empowerment and its influence on the uptake of breast cancer screening in Tanzania: an analysis of 2022 Tanzania demographic health survey data - Maureen Treasure Bamusi; Neena Elezebeth Philip; Lekha D Bhat (BMC, 2024)
Abstract Background Breast cancer is the second most commonly diagnosed cancer worldwide, with a high mortality rate in developing countries, including sub-Saharan Africa. Screening is one way to ensure early detection and management of breast cancer, and it is influenced by several factors. Education and socio-economic status may also affect the utilization of breast cancer screening services as these impact decision-making. This study aimed to investigate women's empowerment and its influence on the uptake of breast cancer screening among women in Tanzania. Methods This study utilized the 2022 Tanzania Demographic and Health Survey data, and included 4216 women aged 20 to 49 years. Women empowerment variables used include social independence, decision-making, ownership of assets, and attitude towards violence. Statistical Package for Social Sciences version 26 was used for data cleaning and analysis. Descriptive statistics and bivariate analysis were done, including a multivariate logistic regression to assess the level of association between independent variables with breast cancer screening. Results Findings indicate that the prevalence of breast cancer screening is 5.2%. Age, education level, literacy, ownership of assets, attitude towards violence, and decision making are associated with ever going for breast cancer screening. Women aged 45 to 49 years (AOR = 6.28, 95% CI = 6.27-6.28), those with secondary or higher education (AOR 1.1, 95% CI = 1.05-1.06), literate women (AOR = 1.13, 95% CI = 1.13-1.13), those who own a house (AOR = 3.08, 95% CI = 3.08-3.09), who jointly decide on their healthcare with partners on healthcare (AOR = 1.18, 95% CI = 1.18-1.19) had significantly higher odds of going for breast cancer screening. Conclusion Women's empowerment is significantly associated with the likelihood of engaging in breast cancer screening. Empowered women are more likely to undergo screening. Focus should be on empowering women through education, businesses, and community involvement. Country-specific interventions and breast cancer screening awareness campaigns should include empowerment initiatives to promote screening uptake.